CT of the Inferomedial Orbit and the Lacrimal Drainage Apparatus: Normal and Pathologic Anatomy - Russell, Eric J.; Czervionke, Leo; Huckman, Michael; Daniels, David; McLachlan, Daniel (American Journal of Neuroradiology, 1985)
The normal and pathologic CT anatomy of the lacrimal drainage apparatus was examined during study of the orbits, nasal cavity, and paranasal sinuses in 100 patients with a variety of clinical complaints related to the inferomedial orbit. The bony lacrimal fossa, the nasolacrimal canal, and the fluid- or air-filled lacrimal sac and nasolacrimal duct were readily recognized in all cases. The lacrimal fossa and sac are found at the inferomedial orbit and are preseptal structures. Cystic expansion of the lacrimal sac (dacryocystitis) may mimic orbital abscess clinically; however, the radiographic recognition of a cystic, peripherally enhancing mass centered at the lacrimal fossa should exclude postseptal abscess and permit more conservative therapy. Obstruction or invasion of the drainage apparatus by tumor, infection, or posttraumatic scarring is readily depicted by CT. Sagittal/coronal images reformatted from thin transverse axial sections are often useful in defining the origin of an inferomedial orbital mass and its relation to the lacrimal sac when clinical studies and axial CT findings are equivocal.